Manfaat Renungan Pagi Terhadap Ketaatan Siswa - Ester Handayani; Ramses Simanjuntak (JURNAL TRANSFORMASI: Jurnal Teologi dan Kepemimpinan, 2023)
Having a child who is in his teens causes a lot of fear in parents. Parents' biggest fear is the societal impact on their child. Especially if you look at the current conditions, many teenagers are falling into the current of juvenile delinquency due to misassociation. The author can understand the fear experienced by parents because there have been too many bad examples of the influence of association on adolescents. Print and electronic mass media news show that every day there is terrible news about troubled teenagers. They commit crimes, brawls, gangs, taking illegal drugs, drug and alcohol addiction.